Teclistamab and Daratumumab Immune-Based Doublet Therapy for Relapsed/Refractory Multiple Myeloma: the TRIMM-2 Study - Paula Rodriguez-Otero; Daniel Morillo; Anita D'Souza; Donna Reece; Niels van de Donk; Ajai Chari; Bhagirathbhai Dholaria; K. Martin Kortüm; Maria-Victoria Mateos; John T. Mckay; Laura Rosiñol; Anna Sureda; et al. (Blood Advances, 2026)
Teclistamab is the first approved B-cell maturation antigen×CD3 bispecific antibody with weight-based dosing for triple-class-exposed relapsed/refractory multiple myeloma (RRMM). We evaluated the safety and efficacy of teclistamab combined with the anti-CD38 monoclonal antibody daratumumab in the phase 1b TRIMM-2 study. Eligible patients had RRMM (≥3 prior lines of therapy [LOT] or were double-refractory to a proteasome inhibitor and immunomodulatory drug); prior anti-CD38 exposure was permitted. Patients received subcutaneous daratumumab per approved schedule plus weight-based or fixed-dose subcutaneous teclistamab. The primary endpoint was safety; secondary endpoints included overall response rate (ORR) and duration of response (DOR). Progression-free survival (PFS) was an exploratory endpoint. Sixty-one patients received the weight-based recommended phase 2 doses (RP2D; teclistamab 1.5 mg/kg QW or 3.0 mg/kg Q2W); median number of prior LOTs was 5 (range, 1-14). Median follow-up was 12.0-months. The most common treatment-emergent adverse events (TEAEs) were infections, cytokine release syndrome, neutropenia, and anemia; grade 3/4 TEAEs occurred in 93.4% and 7 died from TEAEs. No dose-limiting toxicities occurred. ORR was 68.9% (complete response or better, 44.3%); median DOR was not reached. Median PFS was 26.3 months. A cohort exploring fixed-dose teclistamab (100-300 mg) ended prematurely after a safety signal for fatal infections was identified; out of an abundance of caution, all patients were switched to weight-based dosing. In conclusion, the fully immune-based combination of weight-based RP2D teclistamab plus daratumumab demonstrated deep and durable responses, with a well-characterized safety profile. Results highlight the importance of infection management, including early immunoglobulin replacement. Registered at ClinicalTrials.gov: NCT04108195.